2010
DOI: 10.1080/14616681003727991
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Visa-free Entry on Outbound Tourism: A Case Study of South Korean Travellers Visiting Japan

Abstract: Although visa-free entry is important to tourism flows across borders there has been limited academic research into the effects of this arrangement on international tourism demand. Using the ARIMA, the ARIMA intervention, Winters Exponential Smoothing and theStepwise Autoregressive models, this study examined the effect of visa-free entry on tourism demand between South Korea and Japan, and estimated the impact of this visa-free travel on tourism numbers and receipts. The results showed that for Koreans visiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 41 publications
0
20
1
Order By: Relevance
“…As expected, studies generally find a decrease in relative price in the inbound country increases tourist arrivals. Government policies such as tax credits for tourist expenditures and visa-free entry can also influence demand (Lee et al, 2010). Dimanche (2003) finds that the tax-free shopping program sponsored by the state of Louisiana can be used to attract more tourists and boost their spending on shopping.…”
Section: Determinants Of Tourism Demandmentioning
confidence: 99%
See 2 more Smart Citations
“…As expected, studies generally find a decrease in relative price in the inbound country increases tourist arrivals. Government policies such as tax credits for tourist expenditures and visa-free entry can also influence demand (Lee et al, 2010). Dimanche (2003) finds that the tax-free shopping program sponsored by the state of Louisiana can be used to attract more tourists and boost their spending on shopping.…”
Section: Determinants Of Tourism Demandmentioning
confidence: 99%
“…Although there are unresolved issues regarding territory and events during the Japanese colonial period, a vigorous socio-economic and cultural exchange has arisen between the two countries (Lee et al, 2010). South Korea and Japan, for example, successfully co-hosted the 2002 World Cup and celebrated forty years of diplomatic relations by naming 2005 as the Korea-Japan Friendship Year.…”
Section: Japan's Tourism Relationship With South Koreamentioning
confidence: 99%
See 1 more Smart Citation
“…Goh et al (2008) incorporated a leisure time index and a climate index into monthly demand forecasting and found that they have a stronger impact on tourist arrivals than economic factors. Lee et al (2010) and Song et al (2012b) revealed that visa restriction has a significant negative impact on inbound tourist flows, using South Korea to Japan, China inbound and Hong Kong inbound as their cases. Using a gravity model, Balli et al (2013) further identified that both the international export of Turkish soap operas and termination of the Turkish government's visa requirement policy have increased tourist inflow to Turkey.…”
Section: Other New Explanatory Variablesmentioning
confidence: 99%
“…For instance the method has been used to estimate the influence of visa-free entry on Korean travel to Japan (Lee et al 2010a, b) as well as the impact of terrorist bombings in Bali on tourism (Lee et al 2010a(Lee et al , 2010b. 16 The ARIMA models that emerged from Box andJenkins' (1970, 1976) work form the core of any intervention analysis, and they have been very widely used in forecasting tourist demand more generally.…”
Section: A Simple Time Series Examinationmentioning
confidence: 99%